Arthroscopic Repair of a Posterior Midcapsular Rupture Causing Posterior Shoulder Instability - Gautam P. Yagnik MD; Kevin West MD; Bhavya K. Sheth MD; Luis Vargas MD; John W. Uribe MD (Video Journal of Sports Medicine)
Background: Gross posterior instability is rare and when found likely has an injury or deficiency to the posterior static restraints of shoulder associated with it. Traditionally, injuries to the posterior capsule have been difficult to diagnose and visualize with magnetic resonance imaging preoperatively, and very little literature regarding arthroscopic repair of posterior capsular tears exists currently. Indications: We present a repair of a posterior midcapsular and posterior labral tear in a 26-year-old man with recurrent left posterior shoulder instability using a novel all–arthroscopic technique. Technique Description: We performed a shoulder arthroscopy in a lateral decubitus position with the arm at 45° of abduction using standard posterior viewing and anterior working portals. Diagnostic arthroscopy revealed a large posterior midcapsular rupture approximately 2 cm lateral to the glenoid with an associated posterior labral tear. We created an accessory posterolateral portal with needle localization that was outside the capsular defect yet allowed access to the posterior labrum. Anatomic closure of the capsular tear was achieved arthroscopically with 3 interrupted No. 2 nonabsorbable sutures in a side–to–side fashion. Posterior labral repair and capsular shift were done to further address the instability using 2 knotless all–suture anchors percutaneously placed at the 7 o'clock and 9 o'clock position. We closed the posterior portal with a combination of curved and penetrating suture passers. Incisions were closed with interrupted 4-0 nylon. Postoperatively, the patient was placed in an ultra–sling for 4 weeks before physical therapy. We allowed light strengthening at 8 weeks, full strengthening at 12 weeks, and estimated return to sport at 4 months. Results: At 6 months postoperatively, the patient has regained symmetric motion, full strength, and has no residual pain or instability. Conclusion: Gross posterior instability is a rare and difficult condition to diagnose and manage. If no significant labral injuries are identified, injury to the posterior capsule must be considered and full assessment should be done when visualizing from the anterior portal. Repair of the posterior capsule is necessary and can be achieved all arthroscopically with this technique.